CONCEPTUAL REVIEW OF TEACHERS WORKPLACE SPIRITUALITY AND ITS IMPACT OF TEACHERS INTRINSIC MOTIVATION JOB SATISFACTION AND LIFE SATISFACTION (International Journal of Food and Nutritional Sciences, 2022)
Throughout the length of a student's educational tenure, the educator to play an imperative role in his personality development and the ways in which they relate to the outside world, both intellectually and perceptually. The importance of the educator's role in this area cannot be overstated. Two characteristics that help a teacher have a favourable opinion of the environment in which they work include having a high degree of aspiration and having a positive attitude on the teaching profession. This assessment is based on the teacher's view of the working environment. This study's goal was to assess the literature on spirituality in the workplace with an emphasis on how it affects teachers' levels of intrinsic motivation for their work, job satisfaction, and overall life satisfaction. The model also recommends doing research on the demographically relevant characteristics of the teacher, such as his or her designation, credentials, and years of experience. Additionally, it must be evaluated if organisational components like human resource policies have an impact on the motivation, job satisfaction, and overall well-being of teachers